Effect of Nb doping on microstructure and magnetic properties of hot-deformed Nd-Fe-B magnets with Nd-Cu eutectic diffusion. (20th September 2022) - Song, Tingting; Li, Xin; Tang, Xu; Yin, Wenzong; Luo, Yang; Yu, Dunbo; Yan, Wenlong; Ju, Jinyun; Chen, Renjie; Yan, Aru
Highlights: The added Nb could refine the grain size not only inner the ribbon but also the coarse regions to optimize the microstructure of die-upset magnets. The coercivity was increased from 5.3 kOe to 16.5 kOe for die-upset magnet with Nd70 Cu30 diffusion and Nb addition. The thermal stability of coercivity and remanence is improved with Nb addition. Graphical abstract: Image, graphical abstract Abstract: To restrict grain growth in coarse grain regions caused by the diffusion of Nd-Cu eutectic alloys, the Nb element was introduced into the precursor alloy to regulate the microstructure of melt-spun powder and die-upset magnets. The magnetic properties and thermal stability of die-upset magnets were appreciably improved through the addition of Nb. For the Nb-doped diffusion die-upset magnet, the grains inside the ribbons were refined and the coarse non-oriented surface crystallite got suppressed on the interface of ribbons during the hot-deformation process to form the anisotropic magnet. Moreover, Nd gathers at the intergranular phases, which is considered to enforce domain wall pinning force. The Nb-modified microstructure is advantageous to thermal stability and coercivity enhancement. High-resolution transmission electron microscopy images revealed that the Nb element gathered on the grain boundary and triple grain boundary to form c-Nb and h-NbFeB to hinder the grain growth during the hot-deformation process, which led to direct enhancement in the coercivity. Furthermore, the c-Nb and h-NbFeB are nonmagnetic phases that strengthened the magnetic isolation. However, the h-NbFeB precipitated from the hard magnetic phase and formed crystal defects which led to remanence deterioration.